2022
DOI: 10.1039/d2sc01260j
|View full text |Cite
|
Sign up to set email alerts
|

A cell membrane-targeting AIE photosensitizer as a necroptosis inducer for boosting cancer theranostics

Abstract: Exploration of cellular organelle-specific anchoring photosensitizer with both prominent fluorescence imaging behavior and extraordinary reactive oxygen species (ROS) production capability, is highly in demand but remains a severe challenge for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 59 publications
(75 reference statements)
0
34
0
Order By: Relevance
“…If the cell membrane is damaged, this results in the increased permeability of tumor cells. It may promote the uptake of deleterious material [ 38 , 39 , 40 , 41 ]. There are two main strategies for targeting cell membranes [ 28 ].…”
Section: Organelle-targeting Aie-pdtmentioning
confidence: 99%
See 1 more Smart Citation
“…If the cell membrane is damaged, this results in the increased permeability of tumor cells. It may promote the uptake of deleterious material [ 38 , 39 , 40 , 41 ]. There are two main strategies for targeting cell membranes [ 28 ].…”
Section: Organelle-targeting Aie-pdtmentioning
confidence: 99%
“…Recently, Tang et al designed and synthesized AIE-PSs with NIR-emission (735 nm) that could target cell membranes [ 38 ]. They infused the cationation structure into TBMPEI, triggering the cell-membrane-targeting characterization ( Figure 2 ).…”
Section: Organelle-targeting Aie-pdtmentioning
confidence: 99%
“…11 Niu Niu et al reported a NIR-emitting photosensitizer that targets the cell membrane. 12 Hang Zou et al designed and synthesized a Au complex containing an AIE active group to achieve the two-photon imaging of tumor tissues as well as the PDT treatment of tumor tissues. 13 Although many substances with AIE properties have been reported, they generally rarely regulate AIE properties through ligand modification.…”
Section: Introductionmentioning
confidence: 99%
“…10 Unfortunately, the production of ROS in traditional PDT is always limited due to the hypoxic microenvironment of the tumor and the low permeability of photosensitizers. 11 So far, several effective strategies have been proven to significantly improve the ROS production efficiency of PDT, including using appropriate O 2 carriers (such as hemoglobin or perfluorocarbon) to deliver O 2 directly to the tumor site, 12 improving the oxygenation level in the tumor by inhibiting cell respiration, 13 providing other PDT raw materials, 14 and camouflaging nanoparticles to increase the accumulation of photosensitizers at tumor sites. 15 The combination of a photosensitizer and nanoenzyme is a more effective method to improve the therapeutic effect of ROS mediated PDT.…”
Section: Introductionmentioning
confidence: 99%